Schools as a Framework for COVID-19 Epidemiological Surveillance of Children in Catalonia, Spain: A Population-Based Study - Perramon, Aida; Soriano-Arandes, Antoni; Pino, David; Lazcano, Uxue; Andrés, Cristina; Català, Martí; Gatell, Anna; Carulla, Mireia; Canadell, Dolors; Ricós, Gemma; Riera-Bosch, M. Teresa; Burgaya, Silvia; et al. (Frontiers in Pediatrics, 2021)
Objective: We describe and analyze the childhood (<18 years) COVID-19 incidence in Catalonia, Spain, during the first 36 weeks of the 2020-2021 school-year and to compare it with the incidence in adults. Methods: Data on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) tests were obtained from the Catalan Agency for Quality and Health Assessment. Overall, 7,203,663 SARS-CoV-2 tests were performed, of which 491,819 were positive (6.8%). We collected epidemiological data including age-group incidence, diagnostic effort, and positivity rate per 100,000 population to analyze the relative results for these epidemiological characteristics. Results: Despite a great diagnostic effort among children, with a difference of 1154 tests per 100,000 population in relation to adults, the relative incidence of SARS-CoV-2 for <18 years was slightly lower than for the general population, and it increased with the age of the children. Additionally, positivity of SARS-CoV-2 in children (5.7%) was lower than in adults (7.2%), especially when children were attending school (4.9%). Conclusions: A great diagnostic effort, including mass screening and systematic whole-group contact tracing, was associated with childhood SARS-CoV-2 incidence and lower positivity rate in the 2020-2021 school year. Schools have been a key tool in epidemiological surveillance rather than being drivers of SARS-CoV-2 incidence in Catalonia, Spain.